OCP–FRP protein complex topologies suggest a mechanism for controlling high light tolerance in cyanobacteria - Nikolai N. Sluchanko (Nature Portfolio, 2018)
Cyanobacterial photoprotection is controlled by OCP and FRP proteins, but their dynamic interplay is not fully understood. Here, the authors combine protein engineering, disulfide trapping and structural analyses to provide mechanistic insights into the transient OCP-FRP interaction.